Stem Cell Transplantation in the Treatment of Type 1 Diabetes Mellitus: From Insulin Replacement to Beta-Cell Replacement - Wan, Xin-Xing; Zhang, Dan-Yi; Khan, Md. Asaduzzaman; Zheng, Sheng-Yuan; Hu, Xi-Min; Zhang, Qi; Yang, Rong-Hua; Xiong, Kun (Frontiers in Endocrinology, 2022)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease that attacks pancreatic β-cells, leading to insulitis-related islet β-cell destruction. Islet β-cell transplantation has been proven as a curative measure in T1DM, however, logarithmic increase of global population with diabetes but limited donor supply and need for lifelong immunosuppression restrict the widespread use of β-cell transplantation. Numerous therapeutic approaches were taken to search the substitutes of β-cells, among which, stem cell transplantation is one of the most promising alternatives. Stem cell have demonstrated the potential efficacy to treat T1DM by reconstitution of immunotolerance and preservation of islet β-cell function in recent research. cGMP-grade stem cell products had been used in human clinical trials, showing that stem cells transplantation has beneficial effects on T1DM, with no obvious adverse reactions. To better achieve remission of T1DM by stem cell transplantation, in this work, we explain the progression of stem cell transplantation such as mesenchymal stem cells (MSCs), human embryonic stem cells (hESCs), bone marrow hematopoietic stem cells (BM-HSCs), etc. to restore the immunotolerance and preserve the islet β-cell function of T1DM in recent years. This review article provides the evidences for the clinical applications of stem cell therapy in the treatment of T1DM.